(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2021)
Tuberculosis (TB) is a leading global cause of death and Kenya is among the top 20 countries with a high burden of the disease. Adherence to drugs used to treat the disease remains a crucial challenge towards the elimination of TB in Kenya. This study evaluated the rate and determinants of adherence to TB chemotherapy among adult patients attending health clinics in Nairobi between April and May 2017. A cross-sectional study was carried out in five randomly selected health centres in the Eastlands area of Nairobi involving 113 respondents who voluntarily consented and met the inclusion criteria. Data was collected using a researcher-administered questionnaire and the level of adherence assessed using participants self-reporting. From the results obtained, the participants exhibited low (11, 9.7%), medium (46, 40.7%), and high (56, 49.6%) adherence to TB therapy. Upon stepwise multivariate regression, the absence of a DOT supporter (p=0.039) and being on other medications (p=0.021) were significantly associated with non-adherence. It is inferred that DOT support enhanced adherence while co-morbidities decreased it.